Cover Image. (13th February 2020) - Yu, Cheng; Huang, Yongping; Zhang, Chengbin
Abstract : The cover image is based on the Research Article Role of metal foam in solidification performance for a latent heat storage unit by Cheng Yu et al., https://doi.org/10.1002/er.5069 .